BET proteins are a key component of immunoglobulin gene expression - Shim,JM; Lee,JS; Russell,KE; Wiegman,CS; Barnes,P; Fear,D; Adcock,IM; Durham,AL (Epigenomics, 2017)
Aims:Bromo and extraterminal domain (BET) proteins have been shown to regulate gene expression including inflammatory genes. Methods:In order to investigate the role of the BET proteins in immunoglobulin production we treated the human B cell line CLNH11.4 and primary human B cells and ozone exposed mice with BET inhibitors (JQ1 or IBET151). Results:Both proliferation and IgG production were reduced by JQ1 in a concentration-dependent manner. JQ1 significantly reduced immunoglobulin gene transcription. In vivo treatment of ozone-exposed mice with the BET inhibitor IBET151 similarly inhibited ozone induced immunoglobulin production. JQ1 did not reduce the protein levels of Brd4 or Oct2 per se but reduced the ability of Brd4 and Oct2 to co-immunoprecipitate and of Oct2 to bind to immunoglobulin gene promoters.Conclusions:Our results indicate that BET proteins including Brd4 play a crucial role regulation B cell specific gene expression and immunoglobulin production.